A basic analogue of H-function of two variables - Saxena, R.; Modi, G.; Kalla, S. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In course of an attempt to unify and extend the results of basic hypergeometric functions, the authors define a basic analogue of H-function of two variables and investigate some of its man properties. The basic analogue of H-function of two variables is extended to several variables.